STRATEGI KEWIRAUSAHAAN DI PONDOK PESANTREN MUHAMMAD AL-FATIH SUKOHARJO - Azka Zahro Nafiza; Darsini Darsini; Derita Dwi Prasetyowati; Nur Indah Syafitri; Yuliana Yuliana (Academica: Journal of Multidisciplinary Studies, 2021)
Pondok pesantren is educational institutions that have been successful in empowering people through entrepreneurship programs. The success of such pesantren, certainly influenced by certain factors, one of wich is strategy. This study seeks to examine in depth the strategies implemented by Pondok pesantren Muhammad Al-Fatih Sukoharjo in pursuing entrepreneurship, so that it is able to achieve success. This research uses a qualitative approach with a case study model. Data collection is done by observation, interviews, and documentation. The informants in this study were the caretaker of the pesantren, the manager of the pesantren business unit, and two students who participated in the entrepeneurship program. The data were analyzed by descriptive-analytical method and tested for validity using triangulation technique. The results found that the concept of marketing strategy implemented by this pesantren is: Determine products, determine prices, see market potential, determine market position, prepare to enter the market, determine marketing timing and conduct promotions. This pesantren also has certain strategies to overcome problems in entrepreneurship, such as: Strengthening the mental health through motivation and supondok pesantrenort, teaching parents tips and tricks to deal with diverse communities and breaking the assumptions related to child exploitation.Keywords: Entrepreneurship; Pesantren; Strategy